Sorghum Value Chain Business Case Development - Accelerating Impacts of CGIAR Climate Research for Africa; Financial Access Consulting Services (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Sorghum production is vital to the country’s food security and can play a major role in improving the livelihoods of farmers in arid and semi-arid lands (ASAL). Being a drought resistant crop that can tolerate extreme temperatures and flooding conditions, it offers farmers in ASAL regions a better alternative to generate higher incomes compared to other staples such as maize and wheat. Despite this, uptake of sorghum farming has been slow with production lagging demand nationally. Most farmers have yet to adopt the good agricultural practices (GAP) necessary to boost production. 84.4% of sorghum farmers in Makueni utilize uncertified seeds from their own stored sources while 30.9% of them grow the crop without any fertilizer. The AICCRA project seeks to remedy this by developing a climate-smart lending business case that will encourage financial institutions to lend to these farmers. The business case shall facilitate the formulation of a pilot lending scheme involving a Partner Financial Institution (PFI) covering the semi-arid counties of Kitui and Makueni in Lower Eastern Kenya.